Iodixanol-Induced Hypersensitivity During Coronary Intervention: A Case Report - MS, Druthi; Roy, Subhanita; Masum, Kumar; Srinivas, Sandeep; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice, 2026)
Iodinated contrast media, such as Iodixanol (Visipaque®), are dyes used to improve the clarity of blood vessels and organs during imaging procedures. Iodixanol is a non-ionic, iso-osmolar agent designed to be safer and better tolerated than older contrast dyes. We describe the case of a 48-year-old man with diabetes, high blood pressure, a past stroke, and a seizure disorder who presented with chest pain and was diagnosed with Acute Coronary Syndrome - Anterolateral Wall Myocardial Infarction. He underwent a heart procedure on the left anterior descending artery using Iodixanol. Soon after the dye was given, he developed itching, swelling around the eyes, and red raised patches on the skin, showing an allergic reaction with urticaria and angioedema. He was treated with intravenous antihistamines and steroids, and his symptoms improved. This case highlights that even safer contrast dyes like Iodixanol can cause allergic reactions, stressing the need for close monitoring and timely management.
Keywords: Adverse Drug Reactions; Contrast Media; Iodixanol; Visipaque